A Comprehensive Review on Organic Waste Compost as an Effective Phosphorus Source for Sustainable Agriculture - Lady Johanna Boh´orquez-Sandoval; Jos´e Francisco Garc´ıa-Molano; Jos´e Antonio Pascual-Valero; Margarita Ros-Mu˜noz (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The transformation of Organic Waste through composting has become a source of organic matter that, through microbial action, generates molecules conducive to phosphate solubilization and produces fractions of Po and Pi readily available for plants. For this reason, this review focused on analyzing various research studies where Organic Waste is utilized to release available phosphorus and thus improve agricultural production.